(untitled) (Pakistan Journal of Commerce and Social Sciences (ISSN 1997-8553), 2015)
Objective of this research is to study the effect of Perceived Organizational support at retention of employees with mediation of psychological empowerment in higher educational Institutions of Pakistan. Questionnaire of 31 items is adopted in which 8 item scales is adopted to measure Perceived organizational support, 12 item scale to measure psychological empowerment and 11 item scale to measure Employee retention. 200 questionnaires were distributed, out of which 170 were returned. Analysis of data is done by using SPSS 18 version. Findings of research document the existence of considerable and affirmative association of Perceived organizational support with employee retention by partial mediation of psychological empowerment. In Pakistan this relationship is studied for first time. This study is carried out in Pakistan where perceived organizational support and psychological empowerment have been scarcely investigated and Psychological empowerment is entirely an ignored variable in this regard.